Dynamic conservation and utilization of forest tree genetic resources: indicators for in situ and ex situ genetic conservation and forest reproductive material - Lefèvre, François; Alía, Ricardo; Bakkebo Fjellstad, Kjersti; graudal, Lars; Oggioni, Silvio; Rusanen, Mari; Vendramin, Giovanni Giuseppe; Bozzano, Michele (Euforgen, 2020)
A set of Criteria and Indicators (C&I) for sustainable forest management was adopted by the Forest Europe process as a tool to aid forest policy formulation and decision making, forest monitoring and communication. Six criteria reflect complementary aspects of sustainable forest management in the pan-European region. These are currently being assessed (2019) by a set of 34 quantitative and 11 qualitative indicators. Indicator 4.6 is a quantitative indicator which contributes to Criterion 4 (Maintenance, conservation and appropriate enhancement of biological diversity in forest ecosystems) by focusing on the conservation and use of genetic resources. Between 2016 and 2019 the indicator was revised by a working group established by the EUFORGEN Programme, with the aim of addressing a number of shortcomings in the existing system. The report, Revised indicator on genetic resources (4.6) of the pan-European criteria and indicators for sustainable forest management, addresses the reasoning behind the revision of the indicator and provides details regarding its composition and the reporting of conservation efforts linked to each of the sub-indicators. The revised indicator comprises four sub-indicators: 1. Dynamic conservation (in situ and ex situ) of native species populations; 2. Dynamic conservation (ex situ) of populations of non-native species; 3. Static ex situ conservation; 4. Forest reproductive material production; resulting in informative and comparable verifiers and therefore an improvement in its overall reliability, robustness and resolution. Temporal monitoring of progress made can be carried out using EUFORGEN’s synthetic radar chart representation. I n d i c a t o r o n G e n e t i c R e s o u r c e s xii To ensure the effective use of the revised indicator, the working group gives a number of recommendations: • EUFORGEN member countries should continue to implement and further develop the Pan-European strategy for genetic conservation of forest trees. • Through the EUFORGEN Programme, member countries should work together to develop an agreed set of “minimum requirements” for static ex situ conservation. • Countries should support the development of the national lists of native tree species occurring in each country. With over twenty years of experience in FGR conservation and ten years in managing the EUFGIS information system on in situ conservation units of FGR in Europe, EUFORGEN can guarantee the reliability, specificity, relevance and usefulness of the revised indicator and sub-indicators, which come with a set of more precise definitions and standard scales.
Keywords: forest genetic resources; genetic conservation